The Influence of Lifestyle on Student Learning Outcomes in Social Sciences Subjects at SMPN 5 Satu Atap Wonosari - Putri Rezky Amanda; Roy Hasiru; Fatmawaty Damiti; Meyko Panigoro; Maya Novrita Dama (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of lifestyle on student learning outcomes in social studies at SMPN 5 Satu Atap Wonosari, Boalemo Regency, Gorontalo Province. The study employed a quantitative survey method. Primary data were collected through questionnaires distributed to 36 students of SMPN 5 Satu Atap Wonosari, Boalemo Regency, Gorontalo Province. The data were analyzed using a simple linear regression method. The findings indicated that lifestyle influenced 62% of the students' learning outcomes in social science subject at SMPN 5 Satu Atap Wonosari, Boalemo Regency, Gorontalo Province.